Keputusan Perempuan Menikah Dini - Marta, Afri Rahmadia (Konselor, 2017)
The decision is a process that begins with a planning, implementation, until the stage of control. In decision making to married early women often on several factors causing women should think wisely in determining the right decision. The factors include of education, economic, local culture of the people, peers, parents, and mass media. Research purposes was to find the main factors causing women decided to marry early. Research method used is descriptive with a qualitative approach. A subject of study are women village who has been married at an early age. Technique collect the data is done with a method of interviews and observation. The technique of the processing and analysis of data done by means of descriptive qualitative analysis. The result showed that the decision women village to marry early dominated by cultural factors of the local community condensed by islamic religious culture, education non-formal followed by women until the class two in the pesantren traditional, with the education the female acquiring knowledge about marriage through the book taught by the Tengku, and then existence peers in the homes that many marriage carry out early.